2020
DOI: 10.21203/rs.3.rs-100097/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MSCs‑derived exosomes attenuate ischemia-reperfusion brain injury and inhibit microglia apoptosis via exosomal miR-26a-5p mediated suppression of CDK6

Abstract: Background: This study aims to explore the role of mesenchymal stromal cells (MSCs)-derived exosomes (MSCs-Exo) in the cerebral ischemia-reperfusion (I/R) injury.Methods: Exosomes were isolated from MSCs of adult C57BL/6J mice by the gradient centrifugation method. The expression of miR-26a-5p and CDK6 in MSCs-Exo and mice brain tissues were evaluated by qRT-PCR and western blot. MiR-26a-5p mimics and miR-NC were transfected into MSCs, and exosomes were isolated from the stably expressing MSCs. Then MSCs-Exo-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, direct application of MSCs is associated with potential risks and hazards, especially in babies who are considered a fragile population [5]. Recently, MSCderived exosomes (MSC-exos) have been identified as one of the key neuroprotective mechanisms of MSCs and can effectively ameliorate ischemia/reperfusion-(I/R-) induced brain injury by promoting angiogenesis, regulating immune responses, and inhibiting neuronal apoptosis [6][7][8][9][10]. MSCexos have emerged as an attractive therapeutic alternative that holds great regenerative potential and is cell-free [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, direct application of MSCs is associated with potential risks and hazards, especially in babies who are considered a fragile population [5]. Recently, MSCderived exosomes (MSC-exos) have been identified as one of the key neuroprotective mechanisms of MSCs and can effectively ameliorate ischemia/reperfusion-(I/R-) induced brain injury by promoting angiogenesis, regulating immune responses, and inhibiting neuronal apoptosis [6][7][8][9][10]. MSCexos have emerged as an attractive therapeutic alternative that holds great regenerative potential and is cell-free [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study using human umbilical cord-derived MSCs showed optimistic results in treating vertebral bone defects in weaned rabbits (Cui et al, 2019). Mouse BM-MSCs were shown to attenuate ischemia-reperfusion brain injury and inhibit microglial apoptosis (Cheng et al, 2021). Human umbilical cord MSCs (UC-MSCs) effectively improved renal function and inhibited inflammation and fibrosis in a rat model of diabetic nephropathy (DN) (Xiang et al, 2020).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…MiR-29b-3p in BMSCs-Exos inhibits cell apoptosis by reducing the expression of Bax, cutting caspase3 and up-regulating Bcl-2 ( Hou et al, 2020 ), and promotes neuronal survival by promoting the anti-apoptotic signal cascades ( Zhang Y. et al, 2021 ). MiR-26a-5p in MSC-exosomes inhibits microglial apoptosis by targeting CDK6 ( Cheng et al, 2021 ). Similar to neurons, oligodendrocytes are highly sensitive to hypoxia, oxidative stress, inflammatory mediators, injuries, or injuries induced by infection.…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%